Akibat Hukum terhadap Akta yang Ditunda Pemberian Nomor dan Tanggal dalam Akta Notaris: (Studi Kasus Putusan Pengadilan Negeri Denpasar Nomor 530/Pdt.G/2016/PN.Dps) - Maghfira Dwi (CV Rewang Rencang, 2025)
This research analyzes the legal consequences of deeds with delayed numbering and dating in notarial deeds based on case study of Denpasar District Court Decision Number 530/Pdt.G/2016/PN.Dps. The research method uses normative juridical approach with qualitative analysis. The results show that delayed numbering and dating causes degradation of deed's evidentiary power from authentic deed to private deed due to violation of Article 38 UUJN. Notary's responsibility includes civil aspects in form of compensation, administrative aspects in form of sanctions from Supervisory Council, and code of ethics aspects in form of professional organization sanctions.